Rancang Bangun Sistem Pendukung Keputusan Pemilihan Mahasiswa Berprestasi Menggunakan Metode AHP dan Promethee - Julianto Lemantara; Noor Akhmad Setiawan; Marcus Nurtiantara Aji (Departemen Teknik Elektro dan Teknologi Informasi, Fakultas Teknik, Universitas Gadjah Mada, 2013)
Student affair often has difficulty in determining students that are sent to event because many outstanding students at institution. So far, the sending of students is still intuitive and subjective. Therefore, this research aims to design and build a decision support system that can provide advice to determine the best student that will be sent to the event. In this research, the method of decision support system that is used is combination of AHP and Promethee. In implementation, AHP is executed to get criteria weight. After that, Promethee is executed to determine the order of candidates priority. The purpose of combination is to increase the quality of advice about the selection of students. The result of research shows that with decision support system that is built, student affair can choose the students that are sent to event more quickly, accurately, and objectively.